2009
DOI: 10.1111/j.1582-4934.2008.00668.x
|View full text |Cite
|
Sign up to set email alerts
|

A distinct type of cell in myocardium: interstitial Cajal‐like cells (ICLCs)

Abstract: The existence of a novel type of interstitial cells in the heart, interstitial Cajal-like cells (ICLCs), had been described for the first time in 2005. Their identification was mainly based on ultrastructural criteria: very long (tens up to hundreds of micrometres) and moniliform prolongations, which are extremely thin (less than 0.2 μm), below the resolving power of light microscopy. Myocardial ICLCs were also identified by methylene-blue vital staining, silver impregnation, and immunoreactivity for CD 34, vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
106
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(129 citation statements)
references
References 74 publications
15
106
0
8
Order By: Relevance
“…3B). These latter cells displayed the typical ultrastructural phenotype described previously for cardiac telocytes [5,7,9]. In the newborn heart, such telocytes were found closely Fig.…”
Section: Transmission Electron Microscopysupporting
confidence: 76%
See 2 more Smart Citations
“…3B). These latter cells displayed the typical ultrastructural phenotype described previously for cardiac telocytes [5,7,9]. In the newborn heart, such telocytes were found closely Fig.…”
Section: Transmission Electron Microscopysupporting
confidence: 76%
“…Of note, stromal cells bearing long cellular extensions have been also described in most mature organs, although they have been long neglected and simplistically labelled as fibroblasts. However, this view is being rapidly changing due to the recent observations by Popescu and coworkers who found stellate-shaped stromal cells occurring in several adult tissues and organs, where they may represent a distinct cell type from the classical fibroblasts [5]. [6].…”
Section: In This Line Peculiar Stromal Cells Have Been Identified mentioning
confidence: 99%
See 1 more Smart Citation
“…In some of the cells, PDE2 was found co-localized with vimentin, a specific feature of ICs and neurons, thereby confirming earlier findings describing immunolabeling for ICs in cardiac tissue and the urogenital tract (Figure 3c). [13][14][15][16][17] Staining specific for PDE11A (dual-substrate PDE) was observed in single nerve trunks located in the clitoral stroma (Figure 1f). In contrast, no labeling indicating PDE2 or PDE5 was observed in nerve fibers or nerve endings (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…23 26,27 ICs have also been identified by immunoreactivity for the transmembrane receptor protein c-kit, the gap junction protein connexin 43 or vimentin, an intermediate filament subunit of mesenchymal cells. 13,14,16 Usually, ICs can be found adjacent to their target cells, such as smooth muscle cells, epithelial cells or nerve endings. 28 It has been suggested that ICs may have a pivotal role as so-called pacemakers and mediators of neurotransmission in the bladder, urethra and penile erectile tissue.…”
Section: Discussionmentioning
confidence: 99%